Mengurangi Perilaku Hiperaktif Pada Anak Tunagrahita Ringan Melalui Teknik Extinction - Debi Puji Utari; Marlina Marlina (Universitas Negeri Padang, 2018)
In each child there is a unique ability or potential for him. And children's rights (child rights) which states that all children have the same rights and obligations to live and thrive in full compliance with its potential. The purpose of this study how appropriate interventions for children who have hyperactivity in children light mental retardation ?.Beause in the facts have a low interventions for children who have hyperactivity in children light mental retardation. The subjects a child aged 9 years in the SLBN 1 Pariaman.Data collection techniques are measured using interview with teachers in school, observation, assessment, and duration.Completion of this problem is to use behavior modification using a extinction with method by single subjek research (SSR). Positive reinforcement and modeling for the home which result there was a small reduction in hyperactive behavior.It can be concluded that using extinction shows decreased or reduced hyperactivity.